Standardized Total Tract Digestible Phosphorus Requirement of 25- to 50-lb Pigs - C. M. Vier; F. Wu; S. S. Dritz; M. D. Tokach; M. A. Goncalves; U. A. Orlando; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,080 barrows and gilts (PIC; 337 × Camborough, initial pen average BW of 25.2 ± 0.64 lb) were used in a 21-d trial to determine the standardized total tract digestible (STTD) P requirement of nursery pigs from 25 to 50 lb. Two groups of pigs were weaned at approximately 21 d and allotted to pens according to BW and gender. There were 6 replicate pens per treatment and 23 to 27 pigs per pen. Pens of pigs were randomly allotted to experimental diets based on average BW at d 21 and 24 post-weaning, in a randomized complete block design. The 7 dietary treatments consisted of 0.26, 0.30, 0.33, 0.38, 0.43, 0.48, and 0.53% STTD P. These values represented 80, 90, 100, 115, 130, 145, and 160% of the NRC (2012) requirement estimate for STTD P for pigs weighing between 25 to 55 lb, respectively. Two corn-soybean meal-based diets were formulated to contain 0.26 and 0.53% STTD P by increasing the inclusion of limestone and monocalcium phosphate at the expense of corn, maintaining a similar 1.17:1 to 1.18:1 total Ca:P ratio, with no phytase added to the diets. Diets were blended using a robotic feeding system to achieve the intermediate STTD P levels. Increasing STTD P improved ADG, ADFI, F/G, and final BW (linear, P<0.001). There was also a marginally significant quadratic response for F/G (P = 0.067), with the greatest improvement as STTD P was increased from 0.26% to 0.33%. Income over feed cost also improved linearly through 0.53% STTD P (P<0.001). The grams of STTD P intake per day and grams of STTD P intake per kilogram of gain where growth rate reached a point of diminishing returns in response to increased STTD P were higher than the NRC requirement estimates. For ADG, the linear model demonstrated best fit, estimating the maximum response at greater than 0.53% STTD P. For feed efficiency, modeled as G:F, the best-fitting models were the quadratic polynomial (QP) and broken-line linear (BLL). The QP model estimated the maximum at 0.43%, with 99% of maximum G:F achieved at 0.36% STTD P. The BLL plateau was estimated at 0.34% STTD P. In conclusion, the estimated STTD P requirement for nursery pigs from 25 to 50 lb ranged from 0.34 to at least 0.53% depending on the response criteria and statistical model used, which indicates that the NRC (2012) requirement estimate is lower than what is needed to optimize performance and economic return.
Keywords: growth; phosphorus; nursery pigs